Improving community readiness for change through coalition capacity building: Evidence from a multisite intervention. Issue 4 (31st January 2017) - Anderson‐Carpenter, Kaston D.; Watson‐Thompson, Jomella; Jones, Marvia D.; Chaney, Lisa
Abstract: Often, community coalitions are facilitators of community‐level changes when addressing underage drinking. Although studies have shown that enhancing coalition capacity is related to improved internal functioning, the relationship between enhanced capacity and community readiness for change is not well established. The present study used a pretest–posttest design to examine whether enhancing coalition capacity through training and technical assistance was associated with improved community readiness and coalition‐facilitated community‐level changes. Seven Kansas communities engaged in an intensive capacity building intervention through implementation of the Strategic Prevention Framework. The results indicated strong correlations between increased coalition capacity, changes in community readiness stages, and the number of community changes facilitated. The results suggest that strengthening coalition capacity through training and technical assistance may improve community readiness for change and enable the implementation of community‐wide program and environmental changes.